Constructions of Adolescent Identities within Hogwarts Houses in the Harry Potter Novels by J. K. Rowling - Kivimäki Wilders, Michelle (My University, 2022)
The main purpose of this thesis is to examine how four adolescent characters of four different houses in J. K. Rowling’s Harry Potter books series’ Hogwarts School of Witchcraft and Wizardry construct their identities. These characters are Hermione Granger, Luna Lovegood, Nymphadora Tonks and Draco Malfoy. The aim is to find out whether their identities conform with the characteristics the Sorting Hat imposes on each house. Comprehensive pictures of the identities are formed by establishing what is valuable to them in life and what identity statuses the characters have. I do this with the help of psychoanalytic identity theories by Erik Erikson and James Marcia as well as ideas of philosopher Charles Taylor. The analysis clearly shows some narratives, such as helping friends and fighting for justice, were common to all characters. Every character conformed to the features of their house well. There was, however, a distinction between the female and male character when identity statuses were concerned. The young females had achieved identities whereas the male did not. Also, Draco’s values differed from that of the females, which suggests his life has fundamentally been different from the others. Future research could focus on solely one character, the most notable female character of the series Hermione Granger for instance, with the aim of understanding her influence on young readers. A more detailed assessment of her identity as a young female role model for adolescents constructing their own identities could, for instance, be a fruitful area of future research.
Keywords: identity construction, psychoanalysis, Harry Potter series